Neuropsychological parameters as possible indicators of speech fluency disorder in children - Otašević, Jadranka R; Dobrota Davidović, Nada; Kljajić, Dragana (Vojnosanitetski pregled, 2020)
Background/Aim. Speech disfluency (stuttering) is a multifactor disorder and its aetiology is a big unknown for the experts from various fields. Hemisphere dominance as the highest level in the process of integration of cortical functions is of special significance for the entire development. Praxis and gnosis related cortical organizers are the first to form; they become differentiated and functionally full in early childhood while the process of condensing is completed somewhere around the age of 7. Cortical activity organizers are definitely set at that age and from then on act from one hemisphere which becomes dominant for that function. Laterality is determined by hemisphere dominance, but it occurs as a special phenomenon and it is of great significance for personality. The aim of this research was to examine the influence and the relationship between hemisphere asymmetry on the occurrence of speech disfluency in children. Methods. Sixty children aged 5 to 7 years participated in this research. Thirty children suffer from speech fluency disorder (person who stutters – PWS) and they belong to the experimental group while thirty children are fluent speakers (person who does not stutter – PWNS) and they were the control group. Individual testing was used as a test method. Laterality assessment test was used as an instrument which consists of 5 sub-tests as follows: the assessment of hand-use laterality, the assessment of gestural hand-use laterality, the assessment of foot laterality, the assessment of auditory laterality and the assessment of visual laterality. Results. Gestural hand-use laterality and auditory laterality in the PWS examinees were considerably worse in comparison to the PWNS examinees (χ2 = 11.80, p = 0.002, and χ2 = 10.90, p = 0.003, respectively). Male examinees had worse scores in comparison with female examinees. Conclusion. There are certain changes in establishing a dominant hemisphere and differentiation of laterality in children who stutter in comparison with the children who are fluent speakers, which has been shown by statistically significant difference in accomplishments at the test of gestural hand-use laterality and the test of auditory laterality.